(untitled) (Al-Academy, 2015)
Industrial product is one of the things of daily use and direct interaction with the user, so the ranges of its association to the user, took a varied and multiple aspects. The user today sees the products as things have specifications related directly to the psychology of the user, so he can reflects his values, principles and ideas on the composition of the total structure of the product, making them a means by which manifested the internal entity’s of the user took an external materiality. And then counting the products being things excite positive feelings among different user was a natural result given the complexity of the relationship between the user and the industrial product. So pleasure is one important effects that result from the interaction of the user with the product, which is linked to a scale ranging between satisfaction and dissatisfaction, and ends with joy and fun